Prioritas Pembangunan Daerah dan Pertumbuhan Ekonomi pada Provinsi Daerah Istimewa Yogyakarta - Choiroel Woestho; Ari Sulistyowati (Jurnal Ekonomi, 2021)
This study aims to identify economic sectors which are regional development priorities based on regional influence, regional specialization and sector competitiveness in the Special Region of Yogyakarta Province. The research uses shift-share analysis and multiple regression analysis for components in shift-share analysis, namely Regional Share, Proportionality Shift, Differential Shift on economic growth. The data used is secondary data, namely Gross Regional Domestic Product by business field between 2011 and 2020. From the results of the analysis, it is known that the regional share component has a contribution of 77.43%, proportionality shift of 18.86% and differential shift of 3, 70%. Meanwhile, from the regression analysis, it is known that the regional share and differential shift components have an effect on economic growth, while the proportionality shift component has no effect on economic growth. Sectors that become specialization in the Special Region of Yogyakarta Province include the manufacturing industry sector, the information and communication sector, the construction sector and the education services sector.